Hubungan Antara Perilaku Menyikat Gigi Dan Karies Gigi Pada Anak di Sekolah Dasar Negeri 27 Sungai Sapih Kuranji Kota Padang - Utami, Sri Pandu Pandu (E-Jurnal Medika Udayana, 2024)
Caries is often experienced in mid-childhood 10-12 years which is referred to as a vulnerable period, because it is at that time that milk teeth begin to fall out and the first permanent teeth begin to grow. The 2018 West Sumatra Basic Health Research Results ( Rikesdas ) stated that 41.74% of children aged 10-14 years experience dental caries, while the prevalence of dental caries in Padang City is around 6,154 children, which is 36.71% . The behavior of maintaining community dental health in maintaining oral health is brushing teeth, while brushing teeth is the most important primary prevention action recommended . Research objectives to find out relationship between tooth brushing behavior and dental caries in children at 27 Sungai Sapih Public Elementary School Kuranji, Padang City . The type of research used is quantitative research, namely analytic with an observation approach . The population in this study were all students in grades 4 and 5 at State Elementary School 27 Sungai Sapih Kuranji Padang City, totaling 114 people with total sampling technique. This research was conducted at 27 Sungai Sapih Public Elementary School Kuranji, Padang City. When the research was conducted in November 2022 -February 2023 . Analysis data using Spearman test, data processing using computerized program SPSS IBM version 25.0 . The results of the study showed that the most tooth brushing behavior was moderate, namely 94 people (82.5%), the most dental caries was very low, namely 56 people (49.1%) and there were relationship between tooth brushing behavior and dental caries in children at 27 Sungai Sapih Public Elementary School Kuranji, Padang City. ( p = 0.001 ) . It is recommended for dental health workers to educate schools about the importance of dental and oral care and how to brush their teeth properly and correctly so that they can increase students' knowledge and behavior in brushing their teeth for the better.